Complete chloroplast genome sequence of Annamocarya sinensis (Juglandaceae), an endangered perennial plant - Shi, Yancai (Mitochondrial DNA B Resour, 2019)
Annamocarya sinensis (Juglandaceae) is a tertiary relict tree restricted to southeastern China and northern Vietnam. Here, we first report and characterize its complete chloroplast genome based on Illumina paired-end sequencing data. The complete plastid genome was 160,065 bp, which contained inverted repeats (IR) of 25,786 bp separated by a large single-copy (LSC) and a small single copy (SSC) of 89,759 bp and 18,734 bp, respectively. The cpDNA contains 130 genes, comprising 85 protein-coding genes, 36 tRNA genes, 8 rRNA genes, and one processed pseudogene. The overall GC content of the plastome is 36.3%. The phylogenetic analysis of 18 selected chloroplast genomes demonstrated that A. sinensis was close to the species Carya kweichowensis.